Life's simple 7 and calcific aortic valve stenosis incidence in apparently healthy men and women. (15th October 2018) - Perrot, Nicolas; Boekholdt, S. Matthijs; Mathieu, Patrick; Wareham, Nicholas J.; Khaw, Kay-Tee; Arsenault, Benoit J.
Abstract: Background: Calcific aortic valve stenosis (CAVS) is the most prevalent heart valve disease in Western societies. The American Heart Association 2020 Strategic Impact Goals introduced the concept of ideal cardiovascular health, which includes seven cardiovascular health metrics, namely body mass index, a healthy diet, physical activity, smoking status, blood pressure, fasting plasma glucose and cholesterol levels. Several prospective studies have shown that compared to people who meet few of the criteria of ideal cardiovascular health, those with ideal cardiovascular health have an 80–90% lower risk of cardiovascular events. Whether or not ideal cardiovascular health is associated with CAVS risk is unknown. The purpose of this study was to assess the association between ideal cardiovascular health status and the risk of CAVS. Methods: In this analysis of the EPIC-Norfolk study, 21, 856 participants were followed for 11.5 years and 430 of them developed CAVS. A cardiovascular health score was calculated based on the number of the seven health metrics. Results: In comparison to individuals in the bottom quartile of ideal cardiovascular health (CAVS event rate of 2, 9%), those in the top quartile of the ideal cardiovascular health score had a relative risk of CAVS of 0, 45 (95% CI 0, 31-0, 65, AVS event rate of 0, 8%). Conclusions: In apparently healthy individuals, modifiable clinical and lifestyle-related risk factors for CVD are strongly associated with the risk of CAVS, thereby suggesting that CAVS may be a preventable disease. Highlights: Poor cardiovascular health score is associated with a higher risk of CAVS. Modifiable clinical and lifestyle risk factors are associated with the risk of CAVS. CAVS may be a preventable disease.